Social Media as a Means of Strengthening Religious Moderation in Indonesia (2018-2024) - Topan, Ali (AN NUR: Jurnal Studi Islam, 2025)
Social media in the flow of information technology development and globalization has an impact on human life, such as the rise of hoaxes, hate speech, and other things with SARA nuances. In overcoming intolerance, religious leaders, influencers, YouTubers, celebrities, and TikTokers play an active role in campaigning for religious moderation on social media as a strengthening of religious beliefs. The purpose of the research is to analyze forms of strengthening religious moderation on social media from 2018 to 2024. The reason is that since 2018, religious moderation has become a priority program of the government under the Ministry of Religion, so it is included in the RPJMN. This research is a literature study with historical methods, first Heuristic (Source Collection), primary sources in the form of social media Facebook (Gudurian Network), TikTok (@kemenag_ri & @arugiano), Instagram (@husein_hadar, @saidaqilsiroj53, and @gusmiftah), and YouTube (Deddy Corbuzier). Secondary sources are obtained from books, scientific articles, proceedings, and records that are relevant to the research. Second, Source Criticism. Third, Interpretation. Fourth, Historiography. The study results show that the form of strengthening religious moderation uses social media means, in the form of dialogue posts between religious leaders, quotes on religious texts, Peace, humanity, love, and tolerance, as well as quotes from moderate figures such as Gus Dur. As for its benefits, it can create a harmonious attitude between religious communities in the public space, increase inclusivity and tolerance, both in the virtual world and in the real world, and prevent conflicts and exclusive attitudes.